PREVALENCE OF UROGENITAL SCHISTOSOMIASIS AMONG PRIMARY SCHOOL CHILDREN IN KAFIN MADAKI, GANJUWA LOCAL GOVERNMENT AREA, BAUCHI STATE (Journal of Pure and Applied Sciences (Science Forum), 2026)
Schistosomiasis remains a major public health challenge in sub-Saharan Africa, with Nigeria bearing the highest burden globally. A lack of recent, localized epidemiological data for many endemic areas, including Kafin Madaki in Bauchi State, hinders effective control efforts, thus, this study was initiated to determine the prevalence of infection and the associated risk factors. To achieve this, a cross-sectional study was conducted among 384 primary school children aged 5–13 years, selected through multistage sampling from eight schools in Kafin Madaki. Urine samples were examined for Schistosoma haematobium eggs by sedimentation. A structured questionnaire that assessed sociodemographic and other characteristics was administered. The overall prevalence of schistosomiasis was 6.3%, with all positive cases identified as S. haematobium. Infection was significantly higher (p0.05). Higher prevalence was also observed among pupils whose parents had no formal education, children from large households, users of bush sanitation, users of stream water, and those living close to water bodies. The study showed that urinary schistosomiasis is present at a low prevalence in Kafin Madaki and is influenced by behavioural, socioeconomic, and environmental factors. Integrated control measures involving periodic mass drug administration, health education, improved sanitation, and safe water supply are recommended as measures to curb the spread of infection among the community.Keywords prevalence, urogenital schistosomiasis, children, Bauchi state.